The good, the bad, and the long-term implications of social diversity - Ramos, M.; Hewstone, M. (Emerging Trends in the Social and Behavioral Sciences, 2019)
Demographic trends reveal that modern societies have become more heterogeneous in terms of their ethnic composition. Concerns about social diversity and its implications have received critical scholarly attention and it has become a prominent topic in several social sciences. The recent but already impressive amount of published research has examined the impact of social diversity (e.g., ethnic, religious diversity) on societal variables such as economic performance and neighbourhood trust. However, results from this body of work have been contradictory and a lack of consensus in diversity research has undermined the impact of science on policy. To address this concern, we propose a time-focused perspective in which seemingly contradictory theoretical perspectives can be integrated to provide a coherent account as to why social diversity can potentially yield both negative and positive outcomes. This perspective is discussed in light of its implications for diversity politics. A successful management and planning of these unprecedented demographic changes will dictate the quality of people’s lives.